Complementing community science with xenomonitoring: Understanding the eco-epidemiology of Dirofilaria immitis infection in dogs and mosquitoes - Tamara Szentivanyi; Laura V. González; Ágnes Klein; Zoltán Soltész; László Z. Garamszegi (Parasites & Vectors)
Abstract Background Dirofilariosis is an emerging mosquito-borne disease that particularly affects domestic dogs worldwide but also causes symptoms in humans. Monitoring the distribution of emerging pathogens is essential for understanding the environmental and ecological factors influencing their transmission, which can be used to develop better prevention strategies. Methods We applied both community science and molecular xenomonitoring to assess the occurrence of Dirofilaria immitis in domestic dogs and mosquitoes. Results As part of the community science approach, we collected infection data from 1491 dogs from owners across Hungary, using a questionnaire survey. We found that 321 dogs (21.5%) tested positive for current or past dirofilariosis infection, with the highest prevalence observed in the southeastern (47.8%) and the eastern regions (43.4%) of the country. Age and living conditions affected infection status, with older dogs (aged 5–10 years and over 10 years) and those kept exclusively outdoors showing significantly higher infection rates. Molecular xenomonitoring revealed D. immitis infection in Aedes albopictus, Aedes koreicus, and Aedes vexans, with the highest minimum infection rate (MIR) in Ae. koreicus (28.5). Similar to community science results, the highest infection rates were observed in the southeastern and eastern regions (MIR: 14.9 and 11.6, respectively), but the two approaches generally provided overall similar geographical patterns. Conclusions While xenomonitoring did not detect infections in Central Transdanubia, community science successfully provided host infection data, demonstrating its usefulness in assessing the presence and distribution of the disease. Finally, we emphasize the value of using an integrative approach, combining community science and xenomonitoring for monitoring dirofilariosis, especially in areas where direct pathogen screening is unavailable. Graphical Abstract